Voices from the coalface: Teaching in a highly diverse postgraduate tourism program. (June 2019) - Dimmock, Kay; Weeks, Paul; Ashton-Hay, Sally
Abstract: The higher education sector's reliance on international students, including Australian postgraduate tourism programs, impacts students and staff. Teachers' stories contribute to understanding the complexity involved. This exploratory study collected stories from classroom experiences of a sample of teaching staff working in majority international classrooms. Using narrative inquiry the teachers' revealed experiences ranging from surprise through to challenge. Drawing on assessment feedback as an example, staff were confronted with unexpected situations and a student learning deficit. Their views noted the absence of preparatory advice on student readiness for postgraduate study and learning. Staff created new avenues for students to access learning.